Dispositional Optimism and Quality of Life in Chronic Kidney Disease: A Serial Mediation Model Through Coping Self-Efficacy and Treatment Adherence - Rostami, Mehdi; Soundy , Puffy; Saeidtaleshi , Leila (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study examined the relationship between dispositional optimism and quality of life in adults with chronic kidney disease and tested the serial mediating roles of coping self-efficacy and treatment adherence. A cross-sectional descriptive-correlational study was conducted with 286 adults with stages 3–5 chronic kidney disease or receiving dialysis at clinics and dialysis centers in Ontario, Canada. Participants completed the Life Orientation Test–Revised, Coping Self-Efficacy Scale, End-Stage Renal Disease Adherence Questionnaire, and Kidney Disease Quality of Life 36-Item Short Form. Data were analyzed using Pearson correlations and serial mediation analysis with PROCESS Model 6. Age, sex, disease stage, diagnosis duration, dialysis status, and comorbidity burden were controlled. Indirect effects were evaluated using 10,000 bootstrap resamples and 95% confidence intervals. Dispositional optimism significantly predicted coping self-efficacy, β = .536, p < .001, treatment adherence, β = .189, p = .001, and quality of life, β = .192, p < .001. Coping self-efficacy significantly predicted treatment adherence, β = .354, p < .001, and quality of life, β = .251, p < .001. Treatment adherence significantly predicted quality of life, β = .298, p < .001. The total indirect effect of optimism on quality of life was significant, effect = 0.95, 95% CI [0.69, 1.24]. The serial indirect pathway through coping self-efficacy and treatment adherence was significant, effect = 0.22, 95% CI [0.12, 0.34]. The final model explained 51.2% of overall quality-of-life variance. Dispositional optimism was associated with better quality of life directly and indirectly through coping self-efficacy and treatment adherence, supporting integrated psychological and adherence-focused interventions in chronic kidney disease care.